Mengembangkan Berbahasa Anak Melalui Audio Visual Pada Kelompok B Di Ra Plus Fatahul Wardah - ., Mutia Syaputria; ., Retno Wulandari; ., Fahmi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Language ability is the ability, skill, richness of speech, thoughts and feelings of humans through arbitrary sounds, used to work together, interact and identify themselves in good conversation. Audio visual media is one of the media that can develop language processes in early childhood. This research was conducted to find out how the influence of audio-visual media has on the language skills of early childhood, especially at RA Plus FATAHUL WARDAH Kindergarten, while the object of the research is the process of understanding children's language at RA Plus FATAHUL WARDAH through audiovisual. This type of research is descriptive qualitative. The data collection technique is the case study method. The results of the study were that there was an influence on early childhood language skills at RA Plus FADAHUL WARDAH Palembang City after the audio-visual learning method was applied.